Teaching Idea: Inspiring Students’ Expository Essay Writing Through Song Approach - Adam, Hafiz; Narayanan, Geethanjali; Karim, Rafidah Abd.; Jamaluddin, Juriani (Faculty of Teacher Training and Education, Universitas Terbuka, 2023)
Expository essays are divided into several different types, and the most common ones are: (i) compare and contrast, (ii) definition, (iii) example essay, and (iv) cause and effect. Using songs in the teaching and learning (T&L) of writing skills in higher education can help the adult learners improve their expository essay writing skills. Research have found that using songs in teaching the writing subject can help improve their: (i) idea generation, (ii) motivation, and (iii) reduce writing apprehension. This approach has long been used in the teaching and learning (T&L) of English language in primary education, to help improve the young learners’ language skill improvements. In university settings, this approach carries different results to different learners, yet is still proven to be beneficial at improving their writing skills. To compose an expository essay, the basic structures of: (1) introduction, (2) body paragraphs, and (3) conclusion must be present. The song approach helps the learners build their main ideas and elaborate them better, since song lyrics carry useful additional ideas that speed up the learners’ point developments, make the session much more interesting, and provide them with a relaxing and safe learning environment. Therefore, this study discusses literatures written by various researchers that are relevant to the benefits of song approach in English writing skills in general, among adult learners.